Level of Physical Fitness Athletics of SMA Negeri 8 Rejang Lebong During the Covid 19 Pandemic - Sunggi Prabowo; Dolly Apriansyah; Citra Dewi (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the level of physical fitness at SMA Negeri 8 Rejang Lebong during the Covid-19 Pandemic. This type of research is descriptive quantitative research. The research sample amounted to 30 people. The instrument used in this study was the TKJI test which consisted of: 60 meter running test, body lift test (30 seconds pi, 60 seconds pa), 60 seconds lying down test, vertical jump test and long distance test (1000 mpi, 1,200 mpa). The classification for the results of the Overall Physical Fitness Test conducted by Boys and Girls was concluded that the Physical Fitness Test at SMA Negeri 8 Rejang Lebong conducted by 20 male students and 10 female students was in the medium category, namely as many as 21 students or with a percentage of 70%.